Protein levels and environmental temperature effects on carcass characteristics, performance, and nitrogen excretion of broiler chickens from 7 to 21 days of age - Faria Filho, DE [UNESP]; Rosa, PS [UNESP]; Vieira, BS [UNESP]; Macari, Marcos [UNESP]; Furlan, Renato Luis [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2005)
This trial was conducted to evaluate the utilization of low-protein diets formulated based on the ideal protein concept for broiler chickens from 7 to 21 days of age reared at different environmental temperatures. Nine hundred male Cobb-500® chickens were used. At day seven chicks were distributed according to a completely randomized design in a 3 x 3 factorial with four replications of 25 birds each. It was used three crude protein levels in the diet (21.5; 20.0 and 18.5%) and three environmental temperatures (low, thermoneutral and high). The performance, carcass characteristics (yield and chemical composition), and nitrogen ingestion and excretion were assessed. There was no significant interaction among the factors for the evaluated variables. Environmental temperatures affected differently chicken performance. High environmental temperature resulted in lower weight gain and higher wing fat percentage, whereas cold temperature resulted in higher feed conversion. on the other hand, low-protein diets decreased weight gain, breast yield, nitrogen excretion and influenced breast and wings chemical composition. Birds reared at high environmental temperature showed lower nitrogen intake and excretion. The results showed that the decrease in protein levels from 7 to 21 days of age contributed to lower nitrogen excretion in broiler chickens, but impaired performance and carcass characteristics independent of rearing temperature.
Keywords: Broiler chicks; environmental temperature; Ideal protein; nitrogen excretion; Performance